What might aquinas have said? the outcome of an experiment involving an electrical generator and a capacitor - Kuchel, Philip W.; Sahade, Marcel V. (Diffusion Fundamentals, 2007)
We present a comparison of two forms of analysis applied to a simple experiment in electrodynamics. One uses contemporary physics and the other metaphysics as espoused by the 13th century scholar Thomas Aquinas. The aim is to illustrate an example of scientific abstraction and prediction of experimental outcomes, and the pitfalls of applying simple intuition.